Impact of China's comprehensive financial reform pilot zone on digital transformation of manufacturing companies. Evidence from listed companies - Jianjiang Liu; Jie Cheng; Fidelis Ayangbah (Cogent Economics & Finance, 2023)
The establishment of the pilot financial reform zone is aimed at promoting regional financial supply-side structural reform. By giving localities broader financial autonomy, local governments are incentivized to target the "pain points and blockages" in financial services to the real economy, thus having a significant impact on the development and transformation of micro enterprises. Based on micro data of A-share listed manufacturing enterprises in Shanghai and Shenzhen from 2010-2021, this paper uses the double difference method (DID) to explore the impact of the establishment of a comprehensive financial reform pilot zone on the digital transformation of micro manufacturing enterprises and its mechanism. The results found that the pilot zone of comprehensive financial reform significantly improved the digitalization of manufacturing enterprises. Specifically, it effectively promotes the digital transformation of enterprises by reducing their financing costs and promoting their physical investment levels. In particular, it has had a stronger positive impact on the digital transformation of non-state-controlled enterprises, competitive enterprises, and labor-intensive and technology-intensive manufacturing enterprises. The results of the present study can provide a reference experience for other regions to carry out financial reforms to serve the transformation and upgrading of enterprises.
Keywords: 330; comprehensive financial reform pilot zone; digital transformation of enterprises; double difference model